FENOMENOLOGI NIAT: Antara al-GhazÄlÄ« dan al-SayÅ«thÄ« - Mujiburrahman (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2011)
The evolusionist and functionalist approaches to religion are generally considered less sympathetic if not antipathy to religious phenomena. This is why, some western scholars propose another approach to study religion called â€˜phenomenologicalâ€™ approach. There have been a number of phenomenological studies of religion, but mostly not of Islam. This article tries to fi ll in the gap by describing and analyzing the Islamic conception of intention (niyyah) developed by al-SayÅ«thÄ« and al-GhazÄlÄ«. As a jurist, al-SayÅ«thÄ« explores different formal rules on niyyah in Islamic jurisprudence, while al-GhazÄlÄ« as a Sufi , tries to deepen the meaning of niyyah in relation to oneâ€™s sincerity to God. Apart from this difference, both conceptions of niyya indicate that as believers, Muslims always attempt to live in the sacred space and time, and make their speech and deed sacred based on the niyyah. Thus, niyya is the very basis of Muslim religious life.